Result Paper on Energy Efficient Routing Protocol Design for Wireless Networks: A Comparative Study on Energy Efficient Routing Protocols for Wireless Sensor Networks (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Current situation the Wireless Sensor Network is used daily workings and monitoring or tracking applications. Wireless sensor networks (WSNs) are networks dedicating to detecting, processing and delivering various physical parameters in the scientific, medical, commercial and military applications. However, sensor nodes of wireless sensor networks are powered with limited batteries and they cannot be easily recharged once deployed. The WSN nodes size is very small the advantage is you can embed it with any device or any environment. This is due to the distributed and dynamic topology of WSN which introduces unique requirements in routing protocols that should be met. To be classified as efficient, WSNs must maintain efficient energy consumption and an extended network life time. The synchronization of peer nodes incurs some overhead for installing the communication network. In this paper, we study the various routing protocols and compare among them. we also study the trade-offs between energy and communication overheads, highlighting the advantages and demerits of each routing protocol with the purpose of discovering new research directions. We also check the implementation of LEACH method working and ORCP method working, using this techniques we propose the new ORCP method to lessen the energy utilization when hubs exchanging information to base stations.